2022
DOI: 10.1021/acs.jmedchem.1c01819
|View full text |Cite
|
Sign up to set email alerts
|

Development of Selective Phosphatidylinositol 5-Phosphate 4-Kinase γ Inhibitors with a Non-ATP-competitive, Allosteric Binding Mode

Abstract: Phosphatidylinositol 5-phosphate 4-kinases (PI5P4Ks) are emerging as attractive therapeutic targets in diseases, such as cancer, immunological disorders, and neurodegeneration, owing to their central role in regulating cell signaling pathways that are either dysfunctional or can be modulated to promote cell survival. Different modes of binding may enhance inhibitor selectivity and reduce off-target effects in cells. Here, we describe efforts to improve the physicochemical properties of the selective PI5P4Kγ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…We have previously described approaches to use known PI5P4K ligands to generate tool molecules for these kinase targets . Herein we describe complementary approaches to identify novel ligands through virtual screening (VS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described approaches to use known PI5P4K ligands to generate tool molecules for these kinase targets . Herein we describe complementary approaches to identify novel ligands through virtual screening (VS).…”
Section: Resultsmentioning
confidence: 99%
“…Variation in catalytic site and putative G-loop sequences may account for the large differences in intrinsic in vitro kinase activity between the isoforms (PI5P4Kγ being 2000-fold less active than PI5P4Kα), , although these differences may be attenuated in vivo . Pan-specific PI5P4K inhibitors have recently been identified that have therapeutic effect in oncology settings. , The complexity of the different cellular roles of the PI5P4Ks, and the relevance of these roles to different diseases, suggests that the development of specific tool inhibitors to the different isoforms will enable mechanistic research into these potentially diverse functions. ,, In particular, the generation of a potent, specific inhibitor to PI5P4Kγ will enable further elucidation of the role of this kinase in a variety of diseases and validate its potential as a therapeutic target. , We have previously reported the development of PI5P4Kγ-specific inhibitors, , but these were limited by both modest potency and compromised drug-like properties. Herein we describe the identification of superior tool molecules with low nM PI5P4Kγ inhibition concentrations, good selectivity against other kinases, and optimized drug-like properties, including extended in vivo half-lives and brain penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have been unable to determine the PI5P4Kγ activity for putative inhibitors. Finally, mutation of the PI5P4Kγ catalytic site to the corresponding PIP4Kα G-loop sequence has been an artificial approach used to increase the kinase functional activity and enable the development of an inhibition assay with a useable window (Clarke and Irvine, 2013; Boffey et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…1), which also binds allosterically. This group solved co-crystal structures of compound 40 bound to PI5P4Kγ (PDB codes: 7QIE and 7QPN), determined a K D = 68 nM for PI5P4Kγ, and only found PAK2 as an off-target with <50% residual activity when compound 40 was screened at 10 µM in a panel of 140 protein kinases and 15 lipid kinases (Boffey et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The quinazolin-4-amine compound NIH-12848 was identified as a PI5P4Kγ inhibitor, acting as an allosteric non-ATP-competitive inhibitor that binds to the putative PI5P substrate binding site 109 . Optimization of this scaffold led to compound 40, which binds an allosteric pocket composed of the activation loop, and PI5P4Kγ unique residues 113 . The allosteric PI5P4Kγ inhibitor NCI-504 also targets this site, increasing productive autophagic flux in fibroblasts and leading to disrupted phosphoinositide equilibrium in cells 110 .…”
Section: Table 2 (Continued) | Summary Of Preclinical Inhibitors Of T...mentioning
confidence: 99%